Safety Culture Measurement Among Chinese Undergraduates at a Private University: Development and Validation - Shan Gao; Shan Gao; Chen Chang; Fang Ren; Fei Yu (Frontiers Media S.A., 2022)
Relatively low level of safety culture among undergraduates and the imperfection of safety management system for students in university result in numerous safety problems. Researches on the safety culture of undergraduates in public universities are much more than those in private universities. Aiming to find out the potential and specific factors that affect the safety culture in the former are different from those in the latter, an anonymous questionnaire survey was conducted among 4,531 students in a private university in Shaanxi province, China. Gender, education background, grade, hometown, one-child policy, major, community, and driver's license on their safety beliefs and behaviors are treated as potential factors in the survey. According to the average score of each item, the investigated private university students are lack of safety knowledge, but perform well in traffic safety behavior. The results show that female students show better safety beliefs and safety behaviors than male students whilst the safety beliefs and safety behaviors of the student majoring in medicine is better than those of students in other majors. The students who live in more developed cities, who are from one-child family and who have driving license, show better safety beliefs and safety behaviors than others. The effective community system of mixed majors is conducive to the formation of good safety beliefs and safety behaviors of college students. The results highlighted that universities should formulate the corresponding intervention strategies to prevent safety problems of the college students according to the specific proportion of gender, major distribution and other actual situation.